Quality and safety in long-term care in Ontario: The impact of language discordance - Batista, Ricardo; Prud'homme, Denis; Rhodes, Emily; Hsu, Amy; Talarico, Robert; Reaume, Michael; Guérin, Eva; Bouchard, Louise; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2021)
Objectives This study compared quality indicators across linguistic groups and sought to determine whether disparities are influenced by resident-facility language discordance in long-term care. Design Population-based retrospective cohort study using linked databases. Setting and Participants Retrospective cohort of newly admitted residents of long-term care facilities in Ontario, Canada, between 2010 and 2016 (N=47,727). Individual residents' information was obtained from the Resident Assessment Instrument Minimum Data Set (RAI-MDS) to determine resident's primary language, clinical characteristics, and health care indicators. Measures Main covariates of interest were primary language of the resident and predominant language of the long-term care facility, which was determined using the French designation status as defined in the French Language Services Act. Primary outcomes were a set of quality and safety indicators related to long-term care: worsening of depression, falls, moderate-severe pain, use of antipsychotic medication, and physical restraints. Multivariable logistic regression models were used to assess the impact of resident's primary language, facility language, and resident-facility language discordance on each quality indicator. Results Overall, there were few differences between francophones and anglophones for quality and safety indicators. Francophones were more likely to report pain (10.9% vs 9.9%; P = .001) and be physically restrained (7.3% vs 5.2%; P < .001), whereas a greater proportion of anglophones experienced worsening of depressive symptoms (24.0% vs 22.9%; P = .001). However, quality indicators were generally worse for francophones in Non-Designated facilities, except for pain, which was more commonly reported by francophones in French-Designated facilities. Anglophones were more likely to be physically restrained in French-Designated facilities (6.7% vs 5.1%; P < .001). Conclusions and Implications For francophones, quality indicators tended to be worse in the presence of resident-facility language discordance. However, these findings did not persist after adjusting for individual- and facility-level characteristics, suggesting that the disparities observed at the population level cannot be attributed to linguistic factors alone.

État des connaissances sur la santé et les services de santé aux aînés francophones en contexte linguistique minoritaire - Bouchard, Louise; Savard, Jacinthe; Renaud, Alexandre (Reflets, 2022)
La recherche en santé sur les communautés de langue officielle en situation minoritaire (CLOSM) a connu un essor remarquable ces deux dernières décennies. L’objectif de cet article est de présenter un état des lieux de la recherche effectuée sur la problématique de la santé et des soins destinés aux personnes âgées francophones en situation linguistique minoritaire. Différents thèmes sont abordés tels que la santé et ses déterminants, l’expérience des usagers quant à la langue des services, l’environnement légal et politique des services en français, l’organisation des services et la performance du système de santé. Cette synthèse évaluative de la recherche vise à fournir un outil de mobilisation des connaissances et des pistes d’action pour mieux répondre aux besoins des populations aînées et pour améliorer l’offre de services. Mots-clés : revue de littérature, aînés francophones, santé, services et politiques de santé, minorité de langue officielle, Canada

Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français. Objectif 1 – Portrait de la santé, de l’accès aux services et des besoins en santé des personnes âgées - De Moissac, Danielle; Roch-Gagné, Margaux (Conseil communauté en santé du Manitoba, 2012)
Les aînés francophones du Manitoba représentent une population particulièrement vulnérable en ce qui a trait à la santé et à l’accès aux services de santé dans leur langue maternelle. Des analyses secondaires de l’Enquête de santé dans les collectivités canadiennes suggèrent que de vivre en situation linguistique minoritaire peut influencer la santé (Bouchard et collab., 2009). Certains facteurs sociodémographiques associés aux francophones en situation minoritaire contribuent à des disparités de santé : un taux de vieillissement plus élevé, une sous-scolarisation, un plus faible revenu et un plus grand pourcentage vivant en région rurale (Bouchard et collab., 2009). On reconnait qu’au Manitoba, la population francophone vieillit plus rapidement que la population anglophone et semble être en moins bonne santé que les non francophones du même âge (Chartier et collab., 2012). La sous-scolarisation, l’unilinguisme francophone et l’usage prédominant de la langue maternelle lorsque la santé physique et émotionnelle est en péril contribuent également à un plus grand besoin d’accès des aînés aux services dans leur langue (Allaire et collab., 2010). L’accessibilité aux services de santé en français est limitée, avec seulement près de la moitié des francophones ayant accès à un médecin de famille pouvant offrir ses services en français (de Moissac et collab., 2011). La langue dans laquelle les services de soins de santé sont reçus étant particulièrement importante pour la population vieillissante, il va de soi que la planification des soins de santé en français au Manitoba doit prévoir un accès à des services de qualité et sécuritaires pour les aînés francophones du Manitoba. Cela explique pourquoi le Conseil communauté en santé du Manitoba a ciblé les aînés comme l’un des groupes prioritaires pour recevoir des services en français (CCS, 2009). Le but principal de cet objectif est donc de dresser un portrait de l’état de santé des personnes francophones du Manitoba âgées de 65 ans et plus résidant à Saint-Boniface et à Saint-Vital. Une description de l’état de santé des aînés vivant dans la communauté, des aînés ayant recours aux soins à domicile et des aînés vivant dans un foyer de soins de longue durée sera d’abord présentée. La disponibilité et l’accessibilité des services de santé et des services sociaux en français dans ces quartiers seront ensuite examinées. Enfin, les besoins des aînés en matière de services de santé, tant pour les personnes autonomes que pour les personnes en perte d’autonomie et dépendantes, seront cernés.

Language and culture in the caregiving of people with dementia in care homes - What are the implications for well-being? A scoping review with a Welsh perspective - Martin, Conor; Woods, Bob; Williams, Siôn (Journal of Cross-Cultural Gerontology, 2019)
The loss of language skills is one of the most challenging aspects of living with dementia. This is particularly true for bilingual individuals, who have difficulty in maintaining fluency in more than one language. Language and culture overlap greatly, with potential implications for the well-being of people with dementia (PWD) being cared for in their ‘second’ language or culture. Our aim was to review the available relevant literature, together with an examination of the potential effects of linguistic incongruity on healthcare in general for Welsh speakers in Wales. A literature search yielded 50 articles, which were analysed using the scoping review methodological framework. We found that the presence of cultural and linguistic congruity was beneficial for PWD living in care homes, and that their absence was detrimental. The absence of linguistic congruity is a strong predictor for decreased well-being in people in such settings, due to communication barriers between residents and carers, which result mainly from the loss of PWD’s second language skills. Such barriers may lead to inappropriate care, e.g. being unable to obtain help to self-care, as well as social isolation. This review suggests that strategies need to be developed across the world to accommodate bilingual individuals requiring a care home for their dementia needs. There is a particular dearth of research regarding the influence of bilingualism on the experience of dementia care in those areas of the UK where the indigenous population are most likely to be bilingual (i.e. parts of Wales).

Cognitive health initiative for Francophone seniors in the GTA - Reflet Salvéo; Entité 4 (Options fo Service Models, 2017)
fs-ref-orig: Reflet Salvéo, & Entité 4. (2017). Cognitive health initiative for Francophone seniors in the GTA. Options fo Service Models. fs-code-orig: Reflet Salvéo-2017

The impact of dementia and language on hospitalizations: A retrospective cohort of long-term care residents - Riad, Karine; Webber, Colleen; Batista, Ricardo; Reaume, Michael; Rhodes, Emily; Knight, Braden; Prud’homme, Denis; Tanuseputro, Peter (BMC Geriatrics, 2020)
Background Hospitalizations carry considerable risks for frail, elderly patients; this is especially true for patients with dementia, who are more likely to experience delirium, falls, functional decline, iatrogenic complications, and infections when compared to their peers without dementia. Since up to two thirds of patients in long-term care (LTC) facilities have dementia, there is interest in identifying factors associated with transitions from LTC facilities to hospitals. The purpose of this study was to investigate the association between dementia status and incidence of hospitalization among residents in LTC facilities in Ontario, Canada, and to determine whether this association is modified by linguistic factors. Methods We used linked administrative databases to establish a prevalent cohort of 81,188 residents in 628 LTC facilities from April 1st 2014 to March 31, 2017. Diagnoses of dementia were identified with a previously validated algorithm; all other patient characteristics were obtained from in-person assessments. Residents’ primary language was coded as English or French; facility language (English or French) was determined using language designation status according to the French Language Services Act. We identified all hospitalizations within 3 months of the first assessment performed after April 1st 2014. We performed multivariate logistic regression analyses to determine the impact of dementia and resident language on the incidence of hospitalization; we also considered interactions between dementia and both resident language and resident-facility language discordance. Results The odds of hospitalization were 39% lower for residents with dementia compared to residents without dementia (OR 0.61, 95% CI 0.57–0.65). Francophones had lower odds of hospitalization than Anglophones, but this difference was not statistically significant (OR 0.91, 95% CI 0.81–1.03). However, Francophones without dementia were significantly less likely to be hospitalized compared to Anglophones without dementia (OR 0.71, 95% CI 0.53–0.94). Resident-facility language discordance did not significantly affect hospitalizations. Conclusions Residents in LTC facilities were generally less likely to be hospitalized if they had dementia, or if their primary language was French and they did not have dementia. These findings could be explained by differences in end-of-life care goals; however, they could also be the result of poor patient-provider communication.

Dépistage nutritionnel chez les aînés en établissements de soins de santé : comparaison entre les établissements francophones et anglophones - Villalon, Lita; Laporte, Manon; Carrier, Natalie (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectifs La malnutrition des aînés est un problème répandu dans les hôpitaux et les foyers de soins. Cependant, la pratique du dépistage nutritionnel dans ces milieux est peu connue, particulièrement dans les établissements francophones de soins de santé. Cette étude avait pour objectifs de comparer la situation du dépistage nutritionnel des aînés dans les établissements de soins de santé francophones et anglophones du Nouveau-Brunswick, ainsi que les perceptions et les pratiques des professionnels de la santé. Méthodes Les données sur les paramètres de dépistage ont été puisées directement dans les dossiers médicaux des patients/résidents âgés. Les perceptions et les pratiques de dépistage nutritionnel des professionnels de la santé (médecins, infirmiers, diététistes) ont été recueillies au moyen de questionnaires. Résultats Cinq hôpitaux et 31 foyers de soins de longue durée du Nouveau-Brunswick ainsi que 421 patients/résidents et 457 professionnels de la santé ont participé à l’étude. Des différences significatives quant à la disponibilité des paramètres de dépistage furent observées entre les patients/résidents francophones et anglophones; les francophones bénéficiant moins de certains paramètres de dépistage dont le poids à l’admission, la perte d’appétit et la fraction des repas consommés. Les perceptions des professionnels quant au dépistage nutritionnel varient selon la profession et la langue de l’établissement. Plusieurs obstacles au dépistage nutritionnel sont relevés. Conclusion La disponibilité moindre de paramètres de dépistage dans les milieux francophones et la sous-évaluation de la malnutrition par les médecins et les infirmiers sont des barrières pouvant influencer le dépistage nutritionnel en établissements de soins de santé francophones.